If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2t=8+1/2t-t=11
We move all terms to the left:
2t-(8+1/2t-t)=0
Domain of the equation: 2t-t)!=0We add all the numbers together, and all the variables
t∈R
2t-(-1t+1/2t+8)=0
We get rid of parentheses
2t+1t-1/2t-8=0
We multiply all the terms by the denominator
2t*2t+1t*2t-8*2t-1=0
Wy multiply elements
4t^2+2t^2-16t-1=0
We add all the numbers together, and all the variables
6t^2-16t-1=0
a = 6; b = -16; c = -1;
Δ = b2-4ac
Δ = -162-4·6·(-1)
Δ = 280
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{280}=\sqrt{4*70}=\sqrt{4}*\sqrt{70}=2\sqrt{70}$$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-16)-2\sqrt{70}}{2*6}=\frac{16-2\sqrt{70}}{12} $$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-16)+2\sqrt{70}}{2*6}=\frac{16+2\sqrt{70}}{12} $
| 2r+24/8=2r-18/2 | | x=3/x+2 | | 4/x-4=x | | -7=5(x+2)+8 | | -4x-36=4(3x+3) | | x-25=3(2x-5) | | -9x-9=-3x-63 | | -x-49=2(2x+3) | | x-28=5(4x+2) | | 4(3x-5)-1=-x+5 | | 5x+27=2(x+5)-10 | | 26=2(3x+4) | | 2x-7=2(2x-4)+5 | | -2x-173=124-11x | | 42=2(4x+5) | | 5x-34=2(5x+3) | | 16=4(2x-4) | | 13x–2(X-4)=8x+1 | | 3(5x-3)-1=-4x-29 | | -201-2x=10x+75 | | 3(x-4)-5=2x-26 | | (x-4)-5=2x-26 | | -14x-63=-9x+32 | | -95=6x | | 2x+19=49-3x | | 4=3h-h+2+10 | | 6x-88=13x+171 | | x=4/2x-4 | | 8x+29=−21+3x | | 16=7t-9 | | 24+24x=150+10x | | X(13-2x)=15 |